Impact of an Educational Workshop on Dietitians’ and Dietetics Students’ Self-Efficacy, Knowledge, and Assessment Skills in Fluid and Electrolyte Management - Wright, Lauri; Andoh, Benjamin; Boateng, Laurene; Intiful, Freda (African Journal of Nutrition and Dietetics, 2024)
Hydration plays a crucial role in maintaining health and physiological functions, yet dehydration contributes to morbidity in chronic diseases. Despite the importance of hydration management, research indicates that healthcare professionals, including dietitians, lack sufficient training and confidence in this area. This study aimed to assess the impact of an educational workshop on dietitians' and dietetic students' self-efficacy, knowledge, and assessment skills related to hydration and electrolyte management. A non-randomized, pre-post observational study was conducted among 191 dietitians and dietetic students attending a half-day continuing education program in Ghana. Participants completed pre- and post-surveys assessing self-efficacy, knowledge, and assessment skills. The Wilcoxon signed-rank test was used to evaluate changes in scores. Data were analyzed using IBM SPSS Statistics Version 29, with significance set at p < 0.05. Out of 191 participants, 141 completed both pre- and post-surveys. Significant improvements were observed in self-efficacy (hydration: Z = 8.64, p < 0.001; electrolytes: Z = 8.66, p < 0.001), assessment skills (Z = 7.57, p < 0.001), and knowledge (Z = 7.45, p < 0.001). Both dietitians and students showed similar improvements across all variables. The workshop significantly enhanced participants' confidence, knowledge, and assessment skills in hydration and electrolyte management, addressing critical gaps in their professional training. The findings underscore the need for ongoing, interprofessional education in hydration care. Targeted educational interventions can effectively improve healthcare professionals’ abilities to manage hydration, with implications for better patient care outcomes. Further research is needed to expand these findings across diverse settings.